Modeling of electronic elements of pulse reflectometers based on characteristics of nonlinear functionals - Семенець, В.В.; Аврунін, О.Г.; Мороз, О.М.; Косуліна, Н.Г.; Черенков, О.Д. (Radiotekhnika, 2020)
The method of studying the complex radio electronic elements of the receiving-transmitting path of the reflectometer using the functional method has been considered in the work. The creation of advanced technologies in medicine, biology and agriculture is impossible without the study of physicochemical processes in biological objects at the micro and nanoscale based on the method of dielectric spectroscopy. Analysis of existing methods and means of dielectric spectroscopy shows that they cannot be used to study biological objects due to the limited accuracy of measurements, narrow frequency range, complexity of the measuring instruments complex; a need for specially trained technical staff, a high cost of the equipment used, the fundamental impossibility of measuring the frequency methods of BF biological objects due to their nonlinear properties. To create a database on the dielectric constant of biological objects of agriculture, pulse reflectometers are needed, the structure of which includes complex nonlinear and electronic elements. Therefore, there is a need to develop and describe the main stages of the method of research of nonlinear radio-electronic elements of the receiving-transmitting path of the reflectometer using the functional method. The work is relevant to create a database of the dielectric constant for biological objects of agriculture. According to the results of the work, the possibility has been obtained of determining the Voltaire nuclei for a wide class of nonlinear multidimensional systems using nonlinear input signals, which significantly expands the field of practical application of the functional method for studying nonlinear radio electronic circles, including pulsed reflectometric systems. At the same time, such an important advantage of the nonlinear current method remains as the convenience of constructing programs for analyzing and synthesizing nonlinear devices and computer systems on its basis. In addition, the method of nonlinear input signals allows you to explore the cascade connection of nonlinear systems, both without interaction between the cascades, and linear interaction between the cascades.